STOCK DYNAMICS OF HORSE MACKEREL, MEGALASPIS CORDYLA (LINNAEUS) ALONG NORTHWEST COAST OF INDIA - JAISWAR, A. K.; BIRADAR, R. S.; GULATI, D. K. (Journal of Indian Fisheries Association, 2015)
The stock dynamics of horse mackerel, Megalaspis cordyla, along the northwest coast of India has been studied using length frequency data recorded from commercial landings and trawl catches of researchcum- training vessel M.F.V. Saraswati. The growth parameters for this species has been estimated to be L==54 em and K=0.49 per annum. The natural and fishing mortality for the stock have been worked out to be 0.93 and 0.91 per annum respectively. The study indicated that the stock is fished at a safer fishing mortality level F 0 .1, lower than Fmsy level.